(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The advent of science and technology has greatly enhanced the conversion of agro-industrial wastes into various value-added products to meet the demands of increasing population. The study evaluated the binding properties of pectin isolated from Citrullus lanatus and Cucumis sativus peels in comparison with carboxymethyl cellulose (CMC) and pectin BP in oxytetracycline capsule formulations Methods: Pectin was extracted from Citrullus lanatus and Cucumis sativus peels using standard procedures. Extracted pectin was subjected to phytochemical, organoleptic and spectral analysis and then used to prepare batches of oxytetracycline granules and capsules. Granule flow, capsules properties and drug compatibility studies using Fourier transform infrared (FTIR) analysis were determined. Results: Phytochemical analysis of the powdered peels of C. lanatus and C. sativus showed the presence of alkaloid, saponin, terpenoid and carbohydrate. Percentage yield of pectin were 11.88 and 12.27% for C. lanatus and C. sativus, respectively. Oxytetracycline granules prepared exhibited the following micromeritic properties; Hausner’s ratios - 1.12 to 1.33; Carr’s indices - 11.11 to 32.61(%); angles of repose - 30.47 to 43.89° and flow rates - 1.17 to 5.67 g/sec. Disintegration times of formulated capsules were between 4.86 to 6.87 min and were within pharmacopoeial limits for capsules. FTIR studies showed no interaction between drug and excipients. Dissolution studies revealed decreased drug released with increase in binder concentration. Conclusion: Pectin extracted from the peels of C. lanatus and C. sativus fruits compared favourably with pectin BP and CMC in their binding properties, hence a suitable substitute binder in the formulation of oxytetracycline granules and capsules.